Online learning motivation for Aviation English: Attitude, readiness, and demographic factors - Rochmawati, Laila; Fatmawati; Sukma, Meita Maharani; Sonhaji, Imam (JEES (Journal of English Educators Society), 2021)
Online learning is an ideal technological development that is created and improved according to technology within the present educational context. The purpose of this study was to find out motivation, attitude, and readiness, as well as demographic factors in online learning, applied linguistics in the Civil Aviation Polytechnic of Surabaya cadets. The instruments in this study were online learning motivation, online learning readiness and online learning attitudes Likert scale questions cumulated using quantitative method with multiple linear regression. This study utilized a group of 139 Diploma-3 Aeronautical Communication Officer and Diploma-3 Air Traffic Controller cadets. Study results mentioned that attitude to online learning, readiness of online learning, age, gender, and education are all important predictors of the motivation for education. The results showed that the level of education and readiness of online learning were variables that have a considerable effect on motivation. The outcomes of this research cope with students' online learning motivation problems in Aviation English online learning. HIGHLIGHTS: The factor excluded from the model, with findings inverse to the ranking of the model. The age as a predictive measure of online learning motivation increases the contrast between expectations of technical skills. Educational institutions need to prioritize online learning experiences before learning to deal more efficiently with the problem of on-line learning motivation. The contribution of this research is key to enhancing online learning output for cadets in addressing the online learning motivation issue, while educational institutions may use online learning as the most successful learning platform.